Designing An Intervention Program To Control Glucose Level In Intensive Care Unit (ICU) In King Hussein Medical Center, Royal Medical Services - Hakuz, Neris Musa Ahmad; Al-Tarawneh, Amani Mahmoud; Amireh, Baraah Walied; Alhawari, Husam; Al-Haqeesh, Hiyam; Abeeleh, Jaafar Abu; Alkhatib, Ahed J; Abeeleh, Mahmoud A Abu (European Scientific Journal, ESJ, 2016)
Controlling blood glucose level in ICU is one of the main priorities in ICU to decrease mortality rates and morbidity rates and to decrease the healthcare cost. The main objective of the present study is design and implement an intervention protocol in ICU. The method involved a suggested intervention protocol which was applied for 25 ICU patients and their findings were compared with 25 ICU patients in control group. Study findings showed that the intervention protocol was able to reduce mortality rates, positive blood cultures, decreased morning glucose level in the intervention group compared with control group. As a conclusion, controlling blood glucose level in ICU is considered an appropriate approach and leads to better outcome of the patients.